Repeated Exposure to the “Spice” Cannabinoid JWH-018 Induces Tolerance and Enhances Responsiveness to 5-HT1A Receptor Stimulation in Male Rats - Elmore, Joshua S.; Baumann, Michael H. (Frontiers in Psychiatry, 2018)
Naphthalen-1-yl-(1-pentylindol-3-yl)methanone (JWH-018) is a synthetic compound found in psychoactive “spice” products that activates cannabinoid receptors. Preclinical evidence suggests that exposure to synthetic cannabinoids increases 5-HT2A/2C receptor function in the brain, an effect which might contribute to psychotic symptoms. Here, we hypothesized that repeated exposures to JWH-018 would enhance behavioral responsiveness to the 5-HT2A/2C receptor agonist DOI. Male Sprague-Dawley rats fitted with sc temperature transponders received daily injections of JWH-018 (1.0 mg/kg, sc) or its vehicle for 7 consecutive days. Body temperature and catalepsy scores were determined at 1, 2 and 4 h post-injection each day. At 1 and 7 days after the final repeated treatment, rats received a challenge injection of either DOI (0.1 mg/kg, sc) or the 5-HT1A receptor agonist 8-OH-DPAT (0.3 mg/kg, sc), then temperature and behavioral responses were assessed. Behaviors induced by DOI included wet dog shakes and back muscle contractions (i.e., skin jerks), while behaviors induced by 8-OH-DPAT included ambulation, forepaw treading and flat body posture. On the first day of repeated treatment, JWH-018 produced robust hypothermia and catalepsy which lasted up to 4 h, and these effects were significantly blunted by day 7 of treatment. Repeated exposure to JWH-018 did not affect behaviors induced by DOI, but behavioral and hypothermic responses induced by 8-OH-DPAT were significantly augmented 1 day after cessation of JWH-018 treatment. Collectively, our findings show that repeated treatment with JWH-018 produces tolerance to its hypothermic and cataleptic effects, which is accompanied by transient enhancement of 5-HT1A receptor sensitivity in vivo.